Dietary Supplements and Natural Products: An Update on Their Clinical Effectiveness and Molecular Mechanisms of Action During Accelerated Biological Aging - Chen, Ye; Hamidu, Sherif; Yang, Xintong; Yan, Yiqi; Wang, Qilong; Li, Lin; Oduro, Patrick Kwabena; Li, Yuhong (Frontiers in Genetics, 2022)
Accelerated biological aging, which involves the gradual decline of organ or tissue functions and the distortion of physiological processes, underlies several human diseases. Away from the earlier free radical concept, telomere attrition, cellular senescence, proteostasis loss, mitochondrial dysfunction, stem cell exhaustion, and epigenetic and genomic alterations have emerged as biological hallmarks of aging. Moreover, nutrient-sensing metabolic pathways are critical to an organism’s ability to sense and respond to nutrient levels. Pharmaceutical, genetic, and nutritional interventions reverting physiological declines by targeting nutrient-sensing metabolic pathways can promote healthy aging and increase lifespan. On this basis, biological aging hallmarks and nutrient-sensing dependent and independent pathways represent evolving drug targets for many age-linked diseases. Here, we discuss and update the scientific community on contemporary advances in how dietary supplements and natural products beneficially revert accelerated biological aging processes to retrograde human aging and age-dependent human diseases, both from the clinical and preclinical studies point-of-view. Overall, our review suggests that dietary/natural products increase healthspan - rather than lifespan – effectively minimizing the period of frailty at the end of life. However, real-world setting clinical trials and basic studies on dietary supplements and natural products are further required to decisively demonstrate whether dietary/natural products could promote human lifespan.